1992
DOI: 10.1161/01.atv.12.5.608
|View full text |Cite
|
Sign up to set email alerts
|

Scavenger receptor-independent stimulation of cholesterol esterification in macrophages by low density lipoprotein extracted from human aortic intima.

Abstract: There is a growing body of evidence that suggests that modification of low density lipoprotein (LDL) in the artery wall may contribute to atherogenesis. A number of physiologically plausible modifications have been studied in vitro, including oxidation, aggregation, formation of complexes with giycosaininoglycans, and generation of LDL-immune complexes. Several studies of the properties of LDL extracted from the aortic intima have been published, but these indicate disagreement about both the nature and the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
85
2

Year Published

1997
1997
2005
2005

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(92 citation statements)
references
References 74 publications
5
85
2
Order By: Relevance
“…We have found ultracentrifugally isolated HDL to be more susceptible to tyrosyl radical oxidation than LDL. 3 We have also found recently that activated human monocytes and neutrophils can oxidize HDL by the myeloperoxidase-dependent generation of tyrosyl radical (50). This phagocyte-modified HDL exhibits a pattern of apoprotein cross-linking and enhanced cholesterol efflux capacity identical to that seen in tyrosylated HDL generated in vitro.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…We have found ultracentrifugally isolated HDL to be more susceptible to tyrosyl radical oxidation than LDL. 3 We have also found recently that activated human monocytes and neutrophils can oxidize HDL by the myeloperoxidase-dependent generation of tyrosyl radical (50). This phagocyte-modified HDL exhibits a pattern of apoprotein cross-linking and enhanced cholesterol efflux capacity identical to that seen in tyrosylated HDL generated in vitro.…”
Section: Discussionmentioning
confidence: 71%
“…Low density lipoprotein (LDL) 1 particles containing modifications consistent with in vivo oxidation have been isolated from human atheromatous lesions (2)(3)(4)(5). Numerous potential mechanisms for the oxidation of lipoproteins in vivo have been proposed (6).…”
mentioning
confidence: 99%
“…10,36 This conclusion is consistent with the finding that the extent of oxidative change to aortic LDL, as assessed by electrophoretic mobility or other physical parameters, is less than that required for scavenger receptor-mediated uptake. 37 Second, our observation has potential implications for the formation of both minimally modified LDL and isoprostanes. Oxovaleroyl, glutaroyl, and epoxyisoprostane (the three active moieties identified in minimally modified LDL generated in vitro 38 ) and isoprostanes are secondary lipid oxidation products.…”
Section: Discussionmentioning
confidence: 89%
“…Human atherosclerotic plaques contain modified LDL C-supplemented culture medium. Serum-supplemented culture medium (5%), however, always completely inhibited OxLDL-that share many properties of Cu 2ϩ -OxLDL [12, 45,46]. Suarna et al reported that plaques not only contain oxidized lipids but induced apoptosis even though DHAA levels in the medium most likely did not exceeded 1 µM, too low a concentration for relatively large amounts of vitamin E and C as well.…”
Section: Discussionmentioning
confidence: 99%